Couple-oriented prenatal HIV counseling for HIV primary prevention: an acceptability study - Kamkamidze George; Kulkarni Sanjeevani; Darak Shrinivas; Perez-Then Eddy; Eboko Fred; Butsashvili Maia; Gadgil Mukta; Miric Marija; Tchendjou Patrice T; Orne-Gliemann Joanna; Balestre Eric; du Loû Annabel; et al. (BMC, 2010)
Abstract Background A large proportion of the 2.5 million new adult HIV infections that occurred worldwide in 2007 were in stable couples. Feasible and acceptable strategies to improve HIV prevention in a conjugal context are scarce. In the preparatory phase of the ANRS 12127 Prenahtest multi-site HIV prevention trial, we assessed the acceptability of couple-oriented post-test HIV counseling (COC) and men's involvement within prenatal care services, among pregnant women, male partners and health care workers in Cameroon, Dominican Republic, Georgia and India. Methods Quantitative and qualitative research methods were used: direct observations of health services; in-depth interviews with women, men and health care workers; monitoring of the COC intervention and exit interviews with COC participants. Results In-depth interviews conducted with 92 key informants across the four sites indicated that men rarely participated in antenatal care (ANC) services, mainly because these are traditionally and programmatically a woman's domain. However men's involvement was reported to be acceptable and needed in order to improve ANC and HIV prevention services. COC was considered by the respondents to be a feasible and acceptable strategy to actively encourage men to participate in prenatal HIV counseling and testing and overall in reproductive health services. Conclusions One of the keys to men's involvement within prenatal HIV counseling and testing is the better understanding of couple relationships, attitudes and communication patterns between men and women, in terms of HIV and sexual and reproductive health; this conjugal context should be taken into account in the provision of quality prenatal HIV counseling, which aims at integrated PMTCT and primary prevention of HIV.